Treatment of Waste Extract Lubricating Oil by Catalytic Cracking Process to Produce Light Fractions - Idan, Fatimah Kadhim I; Obyed, Saleem Mohammed (Al-Khwarizmi Engineering Journal, 2019)
The catalytic cracking of three feeds of extract lubricating oil, that produced as a by-product from the process of furfural extraction of lubricating oil base stock in AL-Dura refinery at different operating condition, were carried out at a fixed bed laboratory reactor. The initial boiling point for these feeds was 140 ºC for sample (1), 86 ºC for sample (2) and 80 ºC for sample (3). The catalytic cracking processes were carried out at temperature range 325-400 ºC and initially at atmospheric pressure after 30 minutes over 9.88 % HY-zeolite catalyst load. The comparison between the conversion at different operating conditions of catalytic cracking processes indicates that a high yield was obtained at 375°C, according to gasoline production. The distillation of cracking liquid products was achieved by general ASTM distillation (ASTM D -86) for separation of gasoline fraction up to 220 ºC from light cycle oil fraction above 220 ºC. According to gasoline production, it can be noticed that the condition of the feed with the lowest initial boiling point (80 ºC) (sample 3) made it gives more production of gasoline as compared with the other feeds (sample 1,2). At the best temperature (375 ºC), for the best feed for the production of gasoline (sample (3)), the production of gasoline + kerosene were 19.315, 16.16 and 12.95 wt.% for sample (2, 3 and 1). The RON for the gasoline produced from the catalytic cracking for the feed of the lowest initial boiling point was 92.3.